2020
DOI: 10.1038/s41467-020-18654-8
|View full text |Cite
|
Sign up to set email alerts
|

Laser-induced graphitization of polydopamine leads to enhanced mechanical performance while preserving multifunctionality

Abstract: Polydopamine (PDA) is a simple and versatile conformal coating material that has been proposed for a variety of uses; however in practice its performance is often hindered by poor mechanical properties and high roughness. Here, we show that blue-diode laser annealing dramatically improves mechanical performance and reduces roughness of PDA coatings. Laser-annealed PDA (LAPDA) was shown to be >100-fold more scratch resistant than pristine PDA and even better than hard inorganic substrates, which we attribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 39 publications
2
58
0
1
Order By: Relevance
“…Recently, Messersmith and coworkers demonstrated that, indeed, having both catechols and amines combined in the same functional monomer is advantageous for the final adhesion strength: decoupling the two kinds of functional groups, in fact, prevents cooperative effects with an observable worsening of the adhesive performances [ 89 ]. The same author also showed that mechanical properties of PDA coating can be further enhanced, and the roughness reduced, by treatment with blue-diode laser treatment, inducing graphitization while preserving multifunctionality [ 90 ]. Surface adhesion of PDA and related materials have been investigated in detail also by Lee and coworkers [ 91 ], who demonstrated that the stability of the obtained coatings is widely independent on the chemical composition of the surface itself [ 92 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Messersmith and coworkers demonstrated that, indeed, having both catechols and amines combined in the same functional monomer is advantageous for the final adhesion strength: decoupling the two kinds of functional groups, in fact, prevents cooperative effects with an observable worsening of the adhesive performances [ 89 ]. The same author also showed that mechanical properties of PDA coating can be further enhanced, and the roughness reduced, by treatment with blue-diode laser treatment, inducing graphitization while preserving multifunctionality [ 90 ]. Surface adhesion of PDA and related materials have been investigated in detail also by Lee and coworkers [ 91 ], who demonstrated that the stability of the obtained coatings is widely independent on the chemical composition of the surface itself [ 92 ].…”
Section: Introductionmentioning
confidence: 99%
“…The same chemical species as observed in the C1s spectrum of PDA-A (see Supplementary Fig. 6b) can be identified in the C1s spectra of HNT-PDA samples, namely C-C/C=C (red, observed at a binding energy (BE) of 284.8 eV), C-O/C-N (blue, BE=286.1 eV), C=O/C=N (green, BE=287.5 eV), O=C-O (pink, BE=289.2 eV) bonds and shake-up component at BE of 291.3 eV 18,30,31 . The spectrum of the N1s core level region changes significantly as the polymerization proceeds (see Fig.…”
Section: Xps Analysismentioning
confidence: 99%
“…a) Atomic force microscopy (AFM) images with line-scan profiles, optical microscope images and SEM images of a pristine PDA at 1.9 W and b) AFM images with line-scan profiles, optical microscope images and SEM images of laser-annealed PDA at 1.9 W. Reprinted with permission from Ref. [32]. Copyright 2020, Nature portfolio.…”
Section: Non-np Water Soluble Melaninmentioning
confidence: 99%
“…[7c], [13], [18], [21b], [22], [24], [32], [50g] Films [19], [32] fluorescence induced in these materials is fundamental. In particular, in the case of melanin NP it has not been definitively demonstrated whether the fluorescence comes from the NP themselves or from molecular residuals produced during the treatments applied in order to produce emission.…”
Section: Npmentioning
confidence: 99%